Penerapan Model Pembelajaran Problem Based Learning untuk Mengukur Kemampuan Berpikir Kritis Mahasiswa Calon Guru pada Mata Kuliah Psikologi Pendidikan - Uus Toharudin; Iwan Setia Kurniawan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
This study aims to determine the critical thinking skills of prospective teachers of biology at Pasundan University in the course of educational psychology. Implementation of Problem Based Learning learning model aims to measure students' critical thinking skills. The method used in this study is a quasi-experimental design with Randomized Control Group Posttest, data obtained based on the analysis, the data is described to obtain information or a description of the results of this research. The population in this study were 104 students, the sample in this study were 39 students for the experimental group-1 and 39 students for the experimental group-2. Data collected test data obtained from the test results of students who are given a score based on the indicators. results of research show that the critical thinking skills of prospective teachers of biology in educational psychology courses including category sufficient for the experimental group-1 and category well for the experimental group-2. The average score of the experimental group-1 amounted to 2.73, and the average score of the experimental group-2 by 3.05. Indicators of critical thinking skills at the highest indicator 3 (I-3) with an average of 3.38 for the experimental group-1 and 3.41 for the experimental group-2. Indicators of critical thinking skills are the lowest in two indicators (I-2) that is equal to 2.23 for the experimental group-1 and 2.74 for the experimental group-2. The average percentage of absorption problems in the experimental group-1 amounted to 51.25%, while the experimental group-2 amounted to 57.21%. The results of significance test p-value (0.008). Based on the significance of the test results can be concluded that the experimental group-2 has the critical thinking skills is better than the experimental group-1.